Tri Hita Karana-Based Human Resource Management Practices in Improving Employee Performance - Ni Nyoman Budiartini; M. Rudi Irwansyah; Komang Krisna Heryanda; Ni Luh Wayang Sayang Telagawathi (Dinasti International Journal of Education Management And Social Science, 2025)
This qualitative study examines the implementation of Tri Hita Karana-based Human Resource Management (HRM) practices at Universitas Pendidikan Ganesha (UNDIKSHA) and their impact on employee performance. Using an exploratory case study approach with NVivo qualitative data analysis software, this research involved 25 participants comprising university management, lecturers, and administrative staff. Data were collected through semi-structured interviews, participant observations, focus group discussions, and document analysis. The findings reveal that Tri Hita Karana implementation across three dimensions Parahyangan (spiritual), Pawongan (social), and Palemahan (environmental) significantly enhances employee motivation, collaboration, innovation, and organizational commitment. The study contributes to the understanding of culturally-embedded HRM practices and offers practical insights for organizations integrating local wisdom into modern management.